Effect of clay composite derived hydroxyapatite on activated carbon for biogas production - Jamali, N. S.; Ismail, S. F.; Ibrahim, M. F.; Che Man, H.; Wan Abdul Karim Ghani, W. A.; Abdul Rashid, S. (2025)
Hydroxyapatite (HAp), a calcium phosphate-based nanomaterial, has gained significant attention due to its exceptional biocompatibility. The integration of HAp into Clay-Hydroxyapatite with activated carbon (CHAp) composite offers a novel solution to improve microbial retention, biofilm formation, and overall process stability in biomethane production systems. This study evaluates the effects of clay-hydroxyapatite as bio-media for biomethane production and biofilm formation within a Sequencing Batch Reactor (SBR). The fermentation process utilized synthetic media and cattle dung at 37°C with a hydraulic retention time of 40 days and assessed the effect of CHAp influences microbial performance in Scanning Electron Microscopy (SEM). The results indicated that formulated CHAp achieving a methane productivity rate of 15.9 mmol CH4/L·d, 344 mL/L.d and a methane yield of 8.32 mol CH4/mol TC. The carrier shows stabilization and indicate the capability of bacteria to stabilize from control (229.2 mL/L.d) to formulated CHAp media (344.4 mL/L.d) for biogas production rate and 292.2 mL/L.d to 388.9 mL/L.d to methane production rate, along with biofilm growth from 23.9 g/g CHAp to 44.4 g/g CHAp, when the HRT was reduced from 40 to 14 days. SEM images confirmed the presence of methanogenic microorganisms and this formulation is promising for enhancing biomethane production in SBR systems.